Ixodes tick saliva suppresses the keratinocyte cytokine response to TLR2/TLR3 ligands during early exposure to Lyme borreliosis. Issue 1 (18th October 2015) - Bernard, Quentin; Gallo, Richard L.; Jaulhac, Benoît; Nakatsuji, Teruaki; Luft, Benjamin; Yang, Xiahoua; Boulanger, Nathalie
Abstract: Ixodes hard tick induces skin injury by its sophisticated biting process. Its saliva plays a key role to enable an efficient blood meal that lasts for several days. We hypothesized that this feeding process may also be exploited by pathogens to facilitate their transmission, especially in the context of arthropod‐borne diseases. To test this, we used Lyme borreliosis as a model. This bacterial infection is caused by Borrelia burgdorferi sensu lato transmitted by Ixodes . We co‐incubated Borrelia with human keratinocytes in the presence of poly (I: C), a dsRNA TLR3 agonist generated by skin injury. This induced a strong cytokine response from human primary keratinocytes that was much greater than that induced by Borrelia alone. OspC, a TLR2/1 agonist and a major surface lipoprotein of Borrelia also amplified the process. Interestingly, tick saliva inhibited cytokine responses by keratinocytes to these TLR agonists. We propose that Borrelia uses the immunoprivileged site produced by tick saliva to facilitate its transmission.